Germanys’ strategies to contribute to a European Information Society - Andreas Koch; Florian Schweinle (Netcom)
The paper reviews selected political aims concerning the information and communications technologies (ICT) which have been formulated by the federal states and national institutions due to the ongoing process of a global information society. One essential impact is the eEurope-programs of the European Union, which were passed in 2000 and 2002. A German particularity of translating these programs into national law is the federal structure, i.e. the national state has just a basic condition to promote novel ideas on the sector of ICT. Execution actually takes place at the level of the federal states. In the following, e-Health-, e- Government, and e-Business-projects will be discussed both on a national level and on the level of two selected federal states (North Rhine-Westphalia and Mecklenburg-Western Pomerania).